An investigation of the antimicrobial patterns and associated demographic determinants in bacteria isolated from patients with non-healing wounds at the Pietersburg and Mankweng Hospitals, Limpopo Province - Kaapu, Kabelo Gabriel (My University, 2022)
Background: Wound infections continue to be problematic in clinical practice where empiric treatment of infections is a routine, with non-healing wounds being a burden to the health care system. A gap has been noted between antimicrobial resistance and demographic factors as an existing relationship. This necessitates an investigation of patterns of isolates and susceptibility profiles of microorganisms in wounds to modify the preventative and therapeutic strategies against the resistant strains leading to the stall of wound healing, which could aid in empiric treatment. Objective: The aim of this study was to determine the antimicrobial patterns and their associated demographic determinants in bacteria isolated from patients with non healing wounds at Pietersburg and Mankweng Hospitals, Limpopo Province. Methods: The study was conducted using antimicrobial susceptibility data collected from National Health Laboratory Service through Academic Affairs and Research Management System for the period 2016-2020. A total of 797 Antimicrobial Susceptibility Test results were analysed using Statistical Package for Social Sciences version 27.0. The susceptibility rates for the bacterial isolates by age and gender were calculated. The mean percentages for sensitivity and resistance were also calculated. Pearson’s Chi-square test was used to compare age and gender with drug susceptibility. A p-value of ≤ 0.05 was considered significant. Results: Of the 797 patient Antimicrobial Susceptibility Test results, 372 (46.7%) were males and 425 (53.3%) females, with mean age of 31.42 ± 21.75 years. The most common isolates were, Klebsiella pneumoniae (23%), Pseudomonas aeruginosa (21.7%), Escherichia coli (16%) and Proteus mirabilis (13.5%). Highest percentage of resistance to any antibiotic was amoxicillin, ampicillin (85.15%) then trimethoprim sulfamethoxazole (60.85%), amoxicillin ampicillin (49.1%), tigecycline (46.35%), cefepime (32.7%), gentamycin (25.4%), ciprofloxacin (22.5%), colistin (17.6%), and meropenem (12.3%). Furthermore, the general view of the study is no statistically clinical significance on the effect of age and gender on bacterial resistance although statistical significance was noted on age the resistance Acinetobacter baumannii vi (p=0.018), and gender on K. pneumoniae (p=0.015), P. mirabilis (p=0.024). Major resistance to A. baumannii, K. pneumoniae and P. mirabilis were from female patients. Conclusions: The most effective antibiotics were meropenem, colistin, and ciprofloxacin. The highest number of isolates were K. pneumoniae, E. coli, P. aeruginosa, P. mirabilis and A. baumannii with the most effective antibiotics gentamycin, meropenem, ciprofloxacin, and cefepime. Although the general view of the study is that no statistically clinical significance was noted on the effect of age and gender on bacterial resistance, it is important to note the significant observation that there was an observed relation of age to amoxicillin-clavulanic acid and Ciprofloxacin and gender to amoxicillin ampicillin. As such, there is insufficient evidence that supports the effect of age and gender on antimicrobial susceptibility. The study suggests caution against the use of amoxicillin ampicillin in the treatment of wound infections as it confers low levels of efficacy and high resistance and ultimately the call to revise minimum inhibitory concentrations and critical concentrations of all less effective drugs to increase their efficacy.
Thesis (M.Sc.(Medical Sciences)) -- University of Limpopo, 2022
Keywords: Antimicrobial susceptibility; Demographic determinants; Wound infections; Antimicrobial resistance; Antimicrobial patterns; Wound healing; Wound healing; Patients; Wounds and injuries -- Infections; Antimicrobial polymers; Anti-infective agents; Surgical wound infections